2015
DOI: 10.1007/s11269-015-1080-1
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow Forecast Errors and Their Impacts on Forecast-based Reservoir Flood Control

Abstract: To make full use of water captured by reservoirs in flood seasons, methods such as forecast-based reservoir flood control (i.e., reservoir operation during flood periods based on precipitation or inflow forecasts) have been developed in China in the past few decades. The success of forecast-based reservoir flood control depends heavily on the precision of the precipitation or inflow forecasts. This study analyzes the sources of uncertainty and quantifies it in the process of reservoir flood control based on fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The time series plot of the error and observed discharge indicated the error sequence follows a definite pattern for the observed discharge (Figures 7g and 7h). Thus, error sequences are certainly demonstrating non‐Gaussian and time‐dependent behavior, and there exists a possibility of error modeling to improve the overall model performance (Cho & Kim, 2022; Farchi et al., 2021; Y. Li et al., 2014; Lipponen et al., 2013; Liu et al., 2015; McInerney et al., 2020; Nester et al., 2012; Shen, Ruijsch, et al., 2022; Shen, Wang, et al., 2022; Tajiki et al., 2020; Tian et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time series plot of the error and observed discharge indicated the error sequence follows a definite pattern for the observed discharge (Figures 7g and 7h). Thus, error sequences are certainly demonstrating non‐Gaussian and time‐dependent behavior, and there exists a possibility of error modeling to improve the overall model performance (Cho & Kim, 2022; Farchi et al., 2021; Y. Li et al., 2014; Lipponen et al., 2013; Liu et al., 2015; McInerney et al., 2020; Nester et al., 2012; Shen, Ruijsch, et al., 2022; Shen, Wang, et al., 2022; Tajiki et al., 2020; Tian et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The time series plot of the error versus observed discharge was visually inspected to ensure the existence of any patterns (Cho & Kim, 2022; Shen, Ruijsch, et al., 2022; Shen, Wang, et al., 2022). Further, autocorrelation analysis of the error series is conducted to ensure error values at any time step are independent of the values at previous time steps, that is, error series has no patterns, that is, it is random and time‐independent (Lipponen et al., 2013; McInerney et al., 2020; Nester et al., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, it can be concluded that the error is non‐normal or non‐Gaussian. Thus, it is anticipated that further modelling of the error would improve the overall model performance resulting in an enhanced streamflow PI (Cho & Kim, 2022; Farchi et al., 2021; Lipponen et al., 2013; Liu et al., 2015; Y. Li et al., 2014; McInerney et al., 2020; Nester et al., 2012; Shen, Ruijsch, et al., 2022; Tajiki et al., 2020; Tian et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The alternative to adding variability to weather forcing is to add randomness to the model's initial conditions through ensemble data assimilation (Liu and Gupta 2007;Liu et al 2015). In snowmelt-dominated catchments, Snow Water Equivalent (SWE) is a major factor and can have considerable impact in volumetric seasonal forecasts (Clark and Hay 2004;Franz et al 2008;Zeinivand and De Smedt 2009;Sproles et al 2016).…”
Section: Esp Pre-processingmentioning
confidence: 99%